Cerebrospinal Fluid and Microdialysis Cytokines in Aneurysmal Subarachnoid Hemorrhage: A Scoping Systematic Review - Zeiler, Frederick A.; Thelin, Eric Peter; Czosnyka, Marek; Hutchinson, Peter J.; Menon, David K.; Helmy, Adel (Frontiers in Neurology, 2017)
Objective: To perform two scoping systematic reviews of the literature on cytokine measurement in cerebral microdialysate (CMD) and cerebrospinal fluid (CSF) in aneurysmal subarachnoid hemorrhage (SAH) patients, aiming to summarize the evidence relating cytokine levels to pathophysiology, disease progression, and outcome. Methods: Two separate systematic reviews were conducted: one for CMD cytokines and the second for CSF cytokines. Data Sources: Articles from MEDLINE, BIOSIS, EMBASE, Global Health, Scopus, Cochrane Library (inception to Oct 2016), reference lists of relevant articles, and gray literature were searched Study Selection: Two reviewers independently identified all manuscripts utilizing predefined inclusion/exclusion criteria. A two-tier filter of references was conducted. Data Extraction: Patient demographic and study data was extracted to tables. Results: There were 9 studies identified describing the analysis of cytokines via CMD in 246 aneurysmal SAH patients. Similarly, 20 studies were identified describing the analysis of CSF cytokines in 630 patients. The two scoping systematic reviews demonstrated: 1. Limited literature available on CMD cytokine measurement in aneurysmal SAH with some preliminary data supporting feasibility of measurement and potential association between IL-6 and patient outcome. 2. Various CSF measured cytokines may be associated with patient outcome at 3 to 6 months, including: IL-1ra, IL-6, IL-8 and TNF-a. 3. There is a small literature body supporting an association between acute/subacute CSF TGF levels and the development of chronic hydrocephalus at 2 to 3 months. Conclusions: The evaluation of CMD and CSF cytokines is an emerging area of the literature in aneurysmal SAH. Further large prospective multi-center studies on cytokines in CMD and CSF need to be conducted.